МОДЕЛЮВАННЯ АСИНХРОННИХ МАШИН ІЗ ЗАГАЛЬНИМ ЗОВНІШНІМ МАСИВНИМ РОТОРОМ - Заблодський , М.М.; Плюгін, В.Є.; Чуєнко, Р.М. (Інститут електродинаміки НАН України, Київ, 2018)
A simulation model is developed and transient modes of a double-module induction machine with a common external solid rotor are researched. It is established, that with the counter rotation of magnetic fields, a gearless mode of the steady operation of a double-module induction machine is provided at low rotational speeds of the solid hollow rotor, combined with a screw actuator. References 14, figure 1, table 1.